Development and preliminary validation of the Sjögren's Tool for Assessing Response (STAR): a consensual composite score for assessing treatment effect in primary Sjögren's syndrome. Issue 7 (7th April 2022) - Seror, Raphaele; Baron, Gabriel; Camus, Marine; Cornec, Divi; Perrodeau, Elodie; Bowman, Simon J; Bombardieri, Michele; Bootsma, Hendrika; Gottenberg, Jacques-Eric; Fisher, Benjamin; Hueber, Wolfgang; van Roon, Joel A; et al.
Abstract : Objective: To develop a composite responder index in primary Sjögren's syndrome (pSS): the Sjögren's Tool for Assessing Response (STAR). Methods: To develop STAR, the NECESSITY (New clinical endpoints in primary Sjögren's syndrome: an interventional trial based on stratifying patients) consortium used data-driven methods based on nine randomised controlled trials (RCTs) and consensus techniques involving 78 experts and 20 patients. Based on reanalysis of rituximab trials and the literature, the Delphi panel identified a core set of domains with their respective outcome measures. STAR options combining these domains were proposed to the panel for selection and improvement. For each STAR option, sensitivity to change was estimated by the C-index in nine RCTs. Delphi rounds were run for selecting STAR. For the options remaining before the final vote, a meta-analysis of the RCTs was performed. Results: The Delphi panel identified five core domains (systemic activity, patient symptoms, lachrymal gland function, salivary gland function and biological parameters), and 227 STAR options combining these domains were selected to be tested for sensitivity to change. After two Delphi rounds, a meta-analysis of the 20 remaining options was performed. The candidate STAR was then selected by a final vote based on metrological properties and clinical relevance. Conclusion: The candidate STAR is a composite responder index that includes all main disease features in a single tool and is designed for use as a primary endpoint in pSS RCTs. The rigorous and consensual development process ensures its face and content validity. The candidate STAR showed good sensitivity to change and will be prospectively validated by the NECESSITY consortium in a dedicated RCT.